Damping Low Frequency Oscillations via FACTS-POD Controllers Tuned by Bees Algorithm - Arzeha, Nurul Aziah; Mustafa, Mohd Wazir; Mohamad Idris, Rasyidah (ELEKTRIKA- Journal of Electrical Engineering, 2018)
Power systems are often subject to low frequency electro-mechanical oscillations resulting from electrical disturbances and consequence of the development of interconnection of large power system. Flexible Alternating Current Transmission System (FACTS) devices with Power Oscillation Damping (POD) as the supplemet controller has been recent research interest in damping the oscillation. Bees Algorithm (BA) is applied to optimized the parameters of the FACTS-POD controller. The main objective of optimization is to improve the system stability by moving the electro-mechanical eigenvalues on the s-plane to the left as far as possible. The controller is tested on a 3-machine 9-bus system and simulated in PSAT in MATLAB environment.Â  The system is disturbed by increasing 10% mechanical input to Generator 2 and second disturbance is the system experiencing a three-phase fault. The performance of the system with the FACTS-POD controller is observed in terms of position of electromechanical eigenvalues on s-plane and damping responses of power oscillations where both terms shows significant improvement as compared to the system without FACTS-POD controller.